Hysteroscopic metroplasty for the septate uterus with diode laser: a pilot study. (November 2016) - Nappi, Luigi; Pontis, Alessandro; Sorrentino, Felice; Greco, Pantaleo; Angioni, Stefano
Abstract: Objective: To evaluate the feasibility and safety of office hysteroscopic metroplasty using a 980 nm diode laser. Study design: 18 patients were treated for septate uterus between 2013 and 2016. The indications for hysteroscopic metroplasty were recurrent abortion in 11 of the women and primary infertility in the other seven. We used a 5 mm-office hysteroscope with a diode laser fibre. After exploration of the cavity, the septum was divided with use of the laser fibre. Results: Operating time was 13, 16 ± 1, 33 min. Intraoperative pain was 3, 05 ± 0, 72. No intraoperative or postoperative complications were observed. Follow-up performed 2 months after the hysteroscopic metroplasty confirmed the complete removal of the septum and no evidence of intrauterine synechiae. Conclusion: Office hysteroscopic metroplasty with use of a diode laser is safe and feasible; we believe that vaporization of the septum with a diode laser could reduce the formation of adhesions and consequently reduce the occurrence of septum persistence.